2017
DOI: 10.3389/fgene.2017.00166
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Suggesting Absence of Mitochondrial DNA Methylation

Abstract: Methylation of nuclear genes encoding mitochondrial proteins participates in the regulation of mitochondria function. The existence of cytosine methylation in the mitochondrial genome is debated. To investigate whether mitochondrial DNA (mtDNA) is methylated, we used both targeted- and whole mitochondrial genome bisulfite sequencing in cell lines and muscle tissue from mouse and human origin. While unconverted cytosines were detected in some portion of the mitochondrial genome, their abundance was inversely as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 47 publications
(61 reference statements)
6
112
0
Order By: Relevance
“…Interestingly, about 23% of all C:G to T:A somatic transitions could also be observed in the mitochondrial CpG regions in our dataset (Figure ). Despite that, one cannot exclude that deamination of 5‐methylcytosine is not an issue as the occurrence of mitogenome methylation is still debatable (Mechta, Ingerslev, Fabre, Picard, & Barrès, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, about 23% of all C:G to T:A somatic transitions could also be observed in the mitochondrial CpG regions in our dataset (Figure ). Despite that, one cannot exclude that deamination of 5‐methylcytosine is not an issue as the occurrence of mitogenome methylation is still debatable (Mechta, Ingerslev, Fabre, Picard, & Barrès, ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, mtDNA methylation has been extensively scrutinized as several studies have identified this modification in cell lines and tissue samples of mouse and human origin, in both normal as well as disease conditions, in young versus aged mice, as well as under various conditions of oxidative stress, nutrition, and environmental exposure (Chestnut et al, 2011;Shock et al, 2011;Dzitoyeva et al, 2012;Bellizzi et al, 2013;Pirola et al, 2013;Wong et al, 2013;Ghosh et al, 2014;Baccarelli and Byun, 2015;Saini et al, 2017). Controversial reports observe either the presence or complete absence of mtDNA methylation in the noncoding control region within a short 7S DNA fragment that results in a three-stranded displacement or D-loop structure, as well as within several rRNA, tRNA, and protein encoding genes (Hong et al, 2013;Wong et al, 2013;Ghosh et al, 2014;Liu et al, 2016;Mechta et al, 2017;Mposhi et al, 2017;Matsuda et al, 2018;Owa et al, 2018). It is advantageous to measure methylation within the mitochondrial D-loop, because this region harbors the HSP and LSP elements and is easily accessible to proteins during mtDNA replication and transcription where methylation can directly impact these processes .…”
Section: The Enigma Of Mtdna Methylationmentioning
confidence: 99%
“…The CpG methylation of the mitochondrial genome is highly debated and many recent studies have proven that cytosine methylation is virtually absent in mtDNA . However, methylation of genes encoding for mitochondrial proteins within the nuclear genome is known to participate in regulating gene expression levels and thus the mitochondrial function .…”
Section: Resultsmentioning
confidence: 99%
“…Differentially methylated regions (DMRs) were then extracted (difference in percentage methylation ≥25%, q ≤ 0.01) for each pairwise comparison with the control within 1596 nuclear genes associated with energy metabolism (transcription start site [TSS] −1.5 kb to transcription end site [TES] +1.5 kb). Since extraction of mitochondrial reads from whole‐genome bisulfite data has been reported to be inaccurate and is highly controversial, only nuclear genes were analyzed in this regard. Hierarchical clustering was performed with correlation‐based distance using Ward's method for detecting the impact of methylation around protein‐coding nuclear genes over phenotypic drift.…”
Section: Methodsmentioning
confidence: 99%